A INFLUÊNCIA DO BIM NA REDUÇÃO DE FALHAS DE COMUNICAÇÃO NA GESTÃO DE PROJETOS DE CONSTRUÇÃO CIVIL - Silva, Johnattan Pereira da; Sousa, Lorrayne Correia; Santos, Francielle Coelho dos; Romagnoli, Larsson Diogo Seabra Coelho (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
With the demand for increasingly complex buildings in construction, there is also a need for innovation, adequates and more efficient actions, methods, techniques and tools to manage them. The BIM (Building Information Modeling) is being used as a tool to analyze and facilitate the access to these innovations and to improve the most recurrent design flaws, in the attempt to deliver projects and buildings with fewer flaws, less waste and improvements in the management of the enterprise, construction site and project. Communication was one of the most recurring failures, pointed out by companies that answered a survey conducted by the PMI (Project Management Institute). In an attempt to investigate the BIM's contribution to communication during the project management that are already using this new methodology in Goiânia, some interviews and visits to construction sites, offices and professionals approaching these points were made. The research has shown that there is no way to achieve all the potential benefits that BIM can bring to projects if the project management processes and methodologies are overlooked. It was clear the contribution of BIM on the improvement of project management, especially in communication, the ease of creating and working with tools and collaborative environments.